New insights into the mechanisms of antidepressant therapy - Schloss, Patrick; Henn, Fritz A. (Pharmacology & therapeutics, 2004)
Depressive disorders are among the most frequent psychiatric diseases in the Western world with prevalence numbers between 9% and 18%. They are characterized by depressed mood, a diminished interest in pleasurable activities, feelings of worthlessness or inappropriate guilt, decrease in appetite and libido, insomnia, and recurrent thoughts of death or suicide. Among other findings, reduced activity of monoaminergic neurotransmission has been postulated to play a role in the pathogenesis of depression. Consistent with this hypothesis, most antidepressive drugs exert their action by elevating the concentration of monoamines in the synaptic cleft. However, it is not the enhancement of monoaminergic signaling per se, but rather long-term, adaptive changes that may underlie the therapeutic effect. These include functional and structural changes that are discussed later. In addition, in the last years, evidence has emerged that remissions induced in patients using lithium or electroconvulsive therapy are accompanied by structural changes in neuronal networks thereby affecting synaptic plasticity in various regions of the brain.
Gesehen am 13.10.2020